Young children's making meaning through drawing : using Kinetic School Drawing (KSD) - Ahmed, Iman Osman Mukhtar (Institute of Education, International Islamic University Malaysia, 2013)
Children communicate with their world by creating meaning through their drawings. These drawings received considerable research attention of many scholars. Surprisingly, only few researchers used Kinetic School Drawings (KSD) technique to study school environment and its impact on children. Therefore, the focus of this study is to examine children's perception towards their school environment. The relationship between their school setting, mental health, and academic achievement. An embedded mixed methods design involving qualitative and quantitative methods was utilized in this study. The study involved 36 international school's children aged seven years. Data was collected through one drawing session. The drawings were first analyzed qualitatively using Kinetic School Drawings (KSD) Scoring and Rating System (SRS) by Andrews and Jenzen (1988), and further analyzed quantitatively. The results of the study supported the accrued knowledge on self-expression of children's feelings through drawings. It revealed a significant correlation between children's perception toward their school environment and mental health. It also revealed an insignificant correlation between children's perception toward their school setting and academic achievement. The results also showed that children that are lowachievers show less interest in academic activities by portraying themselves outside the school environment rather than inside. Lastly, the findings indicated that adjustment problems of multicultural students could be identified through drawings. This further confirmed that KSD is a helpful tool that can be used by school psychologist/counsellor and educators in diagnosing children's problems in both practical and academic aspects, as well as in developing hypotheses for further studies. Although, the findings further confirmed that KSD could be more valuable if combined with Kinetic Family Drawing (KFD) when training is provided to the users.